Characterization of Cd2+ biosorption by Pseudomonas sp. strain 375, a novel biosorbent isolated from soil polluted with heavy metals in Southern China. (February 2020) - Xu, Shaozu; Xing, Yonghui; Liu, Song; Hao, Xiuli; Chen, Wenli; Huang, Qiaoyun
Abstract: Water pollution with heavy metals is a global problem. Using microbial adsorbents to remediate water bodies contaminated with heavy metals has been garnering considerable attention. In this study, a cadmium (Cd 2+ )-resistant bacterium, isolated from soil polluted with heavy metals, was characterized as Pseudomonas sp. 375 based on its biochemical characteristics and 16S rRNA gene. The minimum inhibitory concentration (MIC) of Cd 2+ for strain 375 was 6 mM. We evaluated the effects of different parameters, such as initial pH, contact time, and initial Cd 2+ concentration, on Cd 2+ uptake. The data acquired using nonliving biomass were fitted to a Langmuir isotherm model; however, the Freundlich isotherm model showed better fit for data acquired using living biomass. The maximum biosorption capacities were 92.59 mg g −1 and 63.29 mg g −1 for living and nonliving cells, respectively. The kinetics of biosorption was described using a pseudo-second order kinetic model. The tightly bound Cd on the cell wall played a major role in Cd 2+ adsorption for both biosorbents. SEM-EDX analysis also showed that Cd 2+ was bound to the cell wall. FTIR spectral analysis showed that –CH2, –OH, –SO3, CO, N–H, C–N, phosphate, or sulfate functional groups were the main functional sites for the binding of Cd 2+ ions. Effectively Cd 2+ removal from Cd 2+ contaminated water suggested Pseudomonas sp. 375 was an (a) inexpensive, effective, and promising biosorbent that can be used for bioremediation Cd 2+ -contaminated wastewater. Highlights: The bacterial living biomass had better Cd 2+ biosorption capacity than nonliving biomass. Chemical complexation of functional groups played an important role in Cd 2+ adsorption. Biosorbent 375 exhibited good biosorption properties and effective bioremediation ability for Cd 2+ . Strain 375 showed excellent bioremediation potential for various metal ions in real wastewater.